Social Relations in Minangkabau Society from Hamka's Perspective in Tafsir Al-Azhar - Gazali, Hidayatul Azizah; Auliya, Sefri (UIN Mataram, 2024)
Minangkabau is one of the cultures or ethnic groups in Indonesia that remains a popular subject for research from both cultural and religious perspectives. This is understandable given that the traditions within Minangkabau culture offer intriguing aspects for scholars to analyse. For instance, the matriarchal system in Minangkabau presents a paradox between the matrilineal perspective in culture and the patrilineal perspective in religion, showcasing the Minangkabau community's efforts to accommodate and reconcile cultural and religious approaches. This paper aims to explore the social relations within the Minangkabau community from Hamka's perspective as presented in Tafsir Al-Azhar. This study falls into the category of literary research with a qualitative approach. The data sources for this research are drawn from various library references, including the Tafsir Al-Azhar as the primary source and other related books as secondary sources. The data analysis method employed is content analysis. This research indicates that Hamka has a unique reading of social relations in Minangkabau, highlighting the distinctive influence of matriarchal/matrilineal practices on the social order of Minangkabau society. The explanation of social relations in Minangkabau exists in his tafsir as a tool to provide analogies or explanations of the meaning of verses, making them easier for readers to understand, considering that Tafsir predominantly has a social orientation.